2022
DOI: 10.3389/fpsyg.2021.762746
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Repercussions: Office and Residential Emissions in Pakistan

Abstract: The purpose of this study is to find empirical evidence on whether work from home or residential emissions reduces office emissions. Based on existing research the study supports that there are short-term effects on office emissions, i.e., carbon emissions do not outshine the long-term effects. The shift from offices to working from home due to COVID-19 regulations meant more people operating from home as maintaining their position in the market was crucial. The potential research area is to understand how thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Importantly, when it comes to the impact of perceived stress from the COVID-19 pandemic on consumer behavior a recent study found that higher levels of perceived stress increased the likelihood of purchasing bigger quantities of food (Jezewska-Zychowicz et al, 2020 ). Rehmani et al ( 2021 ) conducted a study to find empirical evidence on whether work from home or residential emissions reduces office emissions, and found that emissions stayed in the environment of employees' workplace in both online and offline conditions. Employees were least affected by the various emissions as they worked online instead of working at organizational setups.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, when it comes to the impact of perceived stress from the COVID-19 pandemic on consumer behavior a recent study found that higher levels of perceived stress increased the likelihood of purchasing bigger quantities of food (Jezewska-Zychowicz et al, 2020 ). Rehmani et al ( 2021 ) conducted a study to find empirical evidence on whether work from home or residential emissions reduces office emissions, and found that emissions stayed in the environment of employees' workplace in both online and offline conditions. Employees were least affected by the various emissions as they worked online instead of working at organizational setups.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are supported by who investigated the influence of the ISO 14001 Environmental Management System (EMS) on the fashion and textile industries and discovered some encouraging results. In the author’s opinion, the operations of the textile industry generate large amounts of waste, which was previously dumped in rivers, resulting in water pollution ( Rehmani et al, 2022 ). However, the implementation of ISO 14001 resulted in a reduction in wastage, as well as the proper and systematic disposal of waste through recycling, efficient work procedures, scheduling, and periodic audits.…”
Section: Discussionmentioning
confidence: 99%
“…Using Google Forms, an electronic questionnaire was employed to guarantee a minimum of 384 responses. In reaction to the COVID-19 pandemic like various studies, the online questionnaire was distributed to IT companies registered at P@sha in August 2021 (Irshad et al, 2021; Rehmani et al, 2022). In Pakistan’s high-tech cities, the P@sha questionnaire was issued to more than 1,000 IT companies.…”
Section: Methodsmentioning
confidence: 99%